Executive Functions and Quality of Classroom Interactions in Kindergarten Among 5–6-Year-Old Children - Veraksa, Aleksander; Bukhalenkova, Daria; Almazova, Olga (Frontiers in Psychology, 2020)
According to international longitudinal studies, the quality of preschool education is of great importance for children’s further development. The modern research’s greatest interest in the field of studying the quality of preschool education is precisely the assessment of the relationship between the teacher and children as well as the teaching quality in kindergarten groups. In this regard, the Classroom Assessment Scoring System (CLASS) seems to be the one of the most relevant for the educational environment quality evaluation. The CLASS methodology (which includes emotional support, classroom organization, and instrumental support) is based on the cultural-historical approach, which shows the interaction between students and adults as the main mechanism for child’s development. The aim of this study is to investigate the relationships between different aspects of the classroom organization quality in kindergarten groups and executive functions components (such as cognitive flexibility, inhibitory control, and working memory) in 5–6-year-old children. The quality of classroom interaction was measured by the CLASS. The study used the Dimensional Change Card Sort (DCCS) method to assess cognitive flexibility and the NEPSY-II subtests “Inhibition” to assess inhibitory control and “Memory for Designs” and “Sentences Repetition” to assess visuo-spatial and verbal working memory, respectively. The study was approved by the Ethics Committee of the Faculty of Psychology at Lomonosov Moscow State University. The study involved 26 kindergarten groups in Moscow. While conducting the research, extreme groups were identified (5 with low quality and 10 with high-quality levels of classroom interaction). Then, three kindergarten groups with low level (65 children) and three groups with high level (68 children) of interaction within classroom were selected and compared. The results revealed that children from groups with low level of classroom interaction have higher results in cognitive flexibility tasks when compared with children from groups with high level of interaction. Also, children from groups with high-quality classroom interaction demonstrated higher results in visuo-spatial working memory tasks and inhibitory control tasks as contrasted with children from low-quality groups. These findings attest to the importance of classroom interaction quality for the executive functions development in the preschool age.